Revealing Catalytic Properties of Palladium/Gold Systems toward Hydrogen Evolution, Oxidation, and Absorption with Scanning Electrochemical Microscopy - Schott, Christian M.; Holl, Julia; Zazpe, Raul; Kopp, Michael; Man, Ondřej; Thalluri; Sitaramanjaneya; M.; Rodriguez-Pereira, Jhonatan; Schneider, Peter M.; Song, Kun-Ting; Keles, Emre; et al. (American Chemical Society (ACS), 2025)
Palladium (Pd) is an active catalyst for various reactions, such as hydrogen evolution (HER) and hydrogen oxidation (HOR) reactions. However, its activity can be further optimized by introducing strain and ligand effects from Pd deposition onto suitable substrates like gold (Au). In this study, we use scanning electrochemical microscopy (SECM) to investigate the catalytic properties of such Pd/Au systems. For the HER, a sub-monolayer of Pd (PdML) was electrochemically deposited onto half of a polycrystalline (pc) Au substrate with underpotential deposition (UPD). The localized activity measurements revealed improved HER kinetics for Pd atoms at the Pd/Au border in 0.1 M HClO4. As a consequence, a set of Pd/Au samples with increasing density of Pd/Au borders was synthesized by atomic layer deposition (ALD). These ALD Pd deposits have an increased thickness compared to a sub-monolayer, which makes hydride formation thermodynamically viable. Because of this, the samples were investigated for the HOR/H absorption activity using the redox competition (RC) mode. We highlight the influence of cations in 0.1 M AMOH (AM = Li+, Na+, K+, Rb+, Cs+) electrolytes on the HOR/H absorption activity, displaying higher activities for larger cations: jLiOH < jNaOH < jKOH < jRbOH < jCsOH. From the spatial and temporal resolution of the activity, active spots are identified, which expand with time and diminishing hydrogen concentration in the electrolyte. Additional laser-induced current transient (LICT) experiments confirm the dependency between cation and electrocatalytic activity observed with RC-SECM.